2013
DOI: 10.1007/s11064-013-1115-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the NLRP3 Inflammasome in Cerebral Cortex After Traumatic Brain Injury in a Rat Model

Abstract: Inflammatory response plays an important role in the pathogenesis of secondary damage after traumatic brain injury (TBI). The inflammasome is a multiprotein complex involved in innate immunity and a number of studies have suggested that the inflammasome plays a critical role in a host inflammatory signaling. Nucleotide-binding domain, leucine-rich repeat, pyrin domain containing 3 (NLRP3) is a key component of the NLRP3-inflammasome, which also includes apoptotic speck-containing protein (ASC) with a cysteine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
173
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(198 citation statements)
references
References 38 publications
15
173
1
Order By: Relevance
“…As previously reported [6], we observed that the level of IL-1β in the brain parenchyma reached a peak on day 3 and decreased until day 7 after brain injury.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As previously reported [6], we observed that the level of IL-1β in the brain parenchyma reached a peak on day 3 and decreased until day 7 after brain injury.…”
Section: Discussionsupporting
confidence: 88%
“…Acute elevation of inflammasome proteins, such as ASC, Casp-1 and NLRP1, has been found in the cerebrospinal fluid of TBI patients, and the degree of elevation correlates significantly with the long-term functional outcome [7]. The activation of the NLRP3 inflammasome has been observed in the inflammatory process of TBI [6]. Furthermore, when cocultured with cerebrospinal fluid from TBI patients, neurons show a significant increase in the levels of AIM2 and cleaved Casp-1 [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NLRP3 inlammasomes were found in astrocytes, microglia and cortical neurons in a weightdrop model of TBI in rats [54]. Protein levels of NLRP3, active caspase-1, and IL-18 all gradually increased over the course of 7 days in cortical tissue ipsilateral to the contusion, while levels of IL-1β rose at 6 h post-injury and declined over the course of 7 days to sham levels [54]. In support of the role of NLRP3 in TBI, another animal study showed that the expression of NLRP3, caspase-1, and thioredoxin-interacting protein (TXNIP), a regulator of NLRP3 activity, were all increased in the cerebral cortex of rats at 12 and 24 h post-blast injury [55].…”
Section: The Inlammasome and Pro-inlammatory Cytokine Releasementioning
confidence: 96%
“…The NLRP1 inlammasome can additionally recruit various cell molecular responses including the membrane channel pannexin-1, the X-linked inhibitor of apoptosis protein (XIAP), caspase-5, caspase-11, and P2X purinoreceptor 7 to guide its activation and actions in various cell types [50]. NLRP3 inlammasomes were found in astrocytes, microglia and cortical neurons in a weightdrop model of TBI in rats [54]. Protein levels of NLRP3, active caspase-1, and IL-18 all gradually increased over the course of 7 days in cortical tissue ipsilateral to the contusion, while levels of IL-1β rose at 6 h post-injury and declined over the course of 7 days to sham levels [54].…”
Section: The Inlammasome and Pro-inlammatory Cytokine Releasementioning
confidence: 99%